Regional anesthesia in spine surgery: A narrative review - David Salven; David Sykes; Melissa Erickson; Khoi Than; Peter Grossi; Clifford Crutcher; Miles Berger; W. Michael Bullock; Jeff Gadsden; Muhammad Abd-El-Barr (Journal of Spine Practice, 2023)
Background: Regional anesthesia, which refers to the use of anesthetics to provide analgesia to a specific body part or nervous innervation territory, has become increasingly popular in the field of spine surgery. With the application of these techniques, it has been postulated that patients will require less systemic analgesia, intraoperatively and postoperatively. The authors of this narrative review discuss the common regional anesthetic modalities applied to spine surgery, in addition to patient selection criteria, success in patients with multiple comorbid illnesses, and its adoption by surgeons.